2009
DOI: 10.1002/pon.1465
|View full text |Cite
|
Sign up to set email alerts
|

Home‐based exercise among cancer survivors: adherence and its predictors

Abstract: Objective: Evidence of the benefits of exercise for those treated for cancer has led to exercise interventions for this population. Some have questioned whether cancer patients offered a home-based intervention adhere to the exercise prescribed.Method: We examined exercise adherence in a randomized controlled trial of a 12-week, home-based exercise trial for breast cancer patients. Three adherence outcomes were examined: minutes of exercise participation=week, number of steps taken during planned exercise=week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
167
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(178 citation statements)
references
References 34 publications
(46 reference statements)
8
167
0
1
Order By: Relevance
“…A meta-analysis carried out by Husebo et al (2013) on the relationships between the TTM and PA adherence reported that the TTM framework includes aspects that predict PA adherence in cancer patients, and thus contributes to the understanding of motivational factors of change in PA behavior with this population. However, in a randomized controlled trial of home-based exercise adherence in recently treated breast cancer survivors, Pinto, Rabin and Dunsiger (2009) reported no significant relation between decisional balance and home-based exercise program. Other studies confirmed the presence of an additional set of PA determinants specifically related to the women's health status (Courneya, Jones, Mackey, & Fairy., 2006;Miedema et al, 2008;Milne, Guilfoyle, Gordon, Wallman, & Courneya, 2007;Rogers, McAuley, Courneya, & Verhulst, 2008).…”
Section: La Identificación De Barreras Como Intervención Para Involucmentioning
confidence: 99%
“…A meta-analysis carried out by Husebo et al (2013) on the relationships between the TTM and PA adherence reported that the TTM framework includes aspects that predict PA adherence in cancer patients, and thus contributes to the understanding of motivational factors of change in PA behavior with this population. However, in a randomized controlled trial of home-based exercise adherence in recently treated breast cancer survivors, Pinto, Rabin and Dunsiger (2009) reported no significant relation between decisional balance and home-based exercise program. Other studies confirmed the presence of an additional set of PA determinants specifically related to the women's health status (Courneya, Jones, Mackey, & Fairy., 2006;Miedema et al, 2008;Milne, Guilfoyle, Gordon, Wallman, & Courneya, 2007;Rogers, McAuley, Courneya, & Verhulst, 2008).…”
Section: La Identificación De Barreras Como Intervención Para Involucmentioning
confidence: 99%
“…The concept of perceived behavioural control stems from self-efficacy theory (Bandura, 1997), which, when applied to physical activity, states that individuals with high levels of self-efficacy (also defined as people's beliefs in their abilities) will perceive fewer barriers to physical activity, or be less affected by them. Indeed, self-efficacy has been shown to be a strong and consistent predictor of physical activity adherence in the general population and in cancer survivors (Booth et al, 2000;Pinto et al, 2009;Sternfeld et al, 1999). In order to improve an individual's self-efficacy it is necessary to address the four main information sources by which it is affected: personal accomplishments, vicarious experiences, verbal encouragement and physiological and affective states.…”
Section: Addressing Psychological Barriers To Physical Activitymentioning
confidence: 99%
“…[6][7][8][9][10] Despite this knowledge, a little less than half the patients with CRF do not exercise due to physical, cognitive, and social reasons. 11,12 National clinical practice guidelines for managing cancer related fatigue recommend that healthcare professionals educate and provide exercise counseling by to patients who are in active treatment. and counseling during treatment to motivate women with breast cancer to exercise, thus minimizing their fatigue.…”
Section: 5mentioning
confidence: 99%